Status Kepemilikan Terhadap Karya Cipta Hasil Dari Pengagunaan Artificial Intelligence (AI) Chat GPT Ditinjau Dari UU No 28 Tahun 2014 - Martha Tri Lestari (Majelis: Jurnal Hukum Indonesia, 2026)
This study aims to examine the legal certainty of ownership of works produced by artificial intelligence (AI), specifically ChatGPT, from the perspective of Law Number 28 of 2014 concerning Copyright. The main focus of this research is to answer the question of whether works produced by AI can be copyrighted and to identify the legal challenges arising from the absence of explicit regulations in the Indonesian positive legal system. This study uses a normative juridical method with a statute approach and analysis of primary and supplementary legal materials. The study's findings indicate that, to date, there are no national regulations explicitly governing copyright recognition for works produced autonomously by AI systems. Based on the provisions of Article 1 number 3 of Law Number 28 of 2014, works must arise from human intellectual ability, therefore, AI products do not qualify as works potentially entitled to copyright protection. Therefore, legal reformulation through regulatory updates is needed to provide legal certainty and address challenges in the digital era, as well as prevent potential disputes in the national creative industry.